(untitled) (International Journal of Natural Sciences, 2012)
The effects of some selected fatty acids supplement on hematobiochemical parameters were studied in rat. A total of twenty rats were randomly assigned into four groups. Group A was considered as control and fed with rat pellet. Group B was treated with 20 mg Soybean oil / kg feed, group C with 20 mg Mustard oil/ kg feed and group D with 20 mg Ghee /kg feed. The mean body weight of group B, C and D of 2nd and 3rd observation (30 and 60 days, respectively) was significantly (P> 0.01) higher compared to group A (Control). The highest body weight was observed in 3rd observation and it was 185.00 ± 2.76 g in group D and the lowest was in control group. TLC value of group D increased significantly (P<0.01) compared to control and was also found higher for group of B and C than that of control. Similar results were found for PCV value. DLC value was significant for none of the groups. The serum cholesterol level of group D increased significantly (P<0.01) but it was also found higher for the groups B and C than that of control. Similar results were found for blood glucose level and Serum Glutamic Pyruvic Transaminase (SGPT) where the values of group D increased significantly (P<0.01) compared to control and the values were also found higher for the groups B and C than that of control. DOI: http://dx.doi.org/10.3329/ijns.v2i1.10879 International Journal of Natural Sciences (2012), 2(1): 21-25